Sosialisasi “Edukasi Pajak dan Mudahnya E-Tax Zaman Now” kepada Warga Blok 3 Batam - Yudi Hartanto; Kelvin Kelvin; Heryanto Heryanto; Felix Derry; Jenry Winata; Erika Erika; Calvina Thai; Evelyn Claudia; Delfia Annisa; Venny Venny; Meilyanti Meilyanti; Evelyn Chai; Cindy Cindy; Febri Nurul Anisah; Ivonne Adeline; Winnie Cen; Jennifer Jennifer; Sarah Nakita Simarmata (National Conference for Community Service Project (NaCosPro), 2019)
This study examines the lack of adequate knowledge of residents of Batam Block 3 Lubuk Baja about online taxes. The purpose of this study is to provide an introduction to online tax and to encourage citizens of Block 3 to participate in paying taxes as an Indonesian citizen (WNI). The data collection process was carried out by observing the needs and constraints of local residents, as well as through interviews with the head of RT 01 Block 3 (Mr. Irwansyah). The material obtained from interviews was transcribed and analyzed. The results of the analysis raised 2 themes discussed here: social support and the goal of participation. The study of these two themes is very useful for understanding how to optimally increase the knowledge and motivation of citizens in carrying out online tax payments.